(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Tampubolon YK, Agus A, Hartatik T, Bintara S, Ismaya, Widyobroto BP, Budisatria IGS, Leroy P, Antoine-Moussiaux N, Panjono. 2023. Reproductive performance of Belgian Blue and Wagyu cross cows. Biodiversitas 24: 5352-5358. Double-Muscle (DM) cattle have been used in cattle breeding programs to increase body weight. This research aims to determine the reproductive performance of using DM cattle. Currently, cattle are produced from a cross between two breeds, namely Belgian Blue (BB) cross (50% BB, 50% BX) and Wagyu cross (50% Wagyu, 50% BX). Natural mating was carried out on nine BB cross cows mated with Wagyu cross bulls and nine Wagyu cross cows bred with BB cross cows. After calving, the cows were raised together with their calves for six months prior to weaning. The collected data were analyzed using One-Way analysis of variance. Calving Interval (CI), Cow Reproductivity Index (CRI), calf weaning weight, and Cow Productivity Index (CPI) of BB and Wagyu cross cows were 426.00±24.92 and 411.55±37.52 days, 0.86±0.05 and 0.89±0.08 head/year, 175.53±24.50 and 121.19±19.80 kg, and 148.46±24.61 and 102.41±20.84 kg/year, respectively. There was no significant difference in the CI and CRI between crosses. However, the weaning weight of BB cross calves was higher (p<0.05) than that of Wagyu cross calves, whereas the CPI of BB cross cows was higher (p<0.01) than that of Wagyu cross cows. It was concluded that the best reproductive performance was the BB cross, which had DM blood.